2008
DOI: 10.1111/j.1439-0469.2007.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme degree of chromosome number variability in species of the spider genus Scytodes (Araneae, Haplogynae, Scytodidae)

Abstract: Genus Scytodes includes most species of the spider family Scytodidae. Until now, 187 species of the genus have been described. In spite of this great diversity, only three Scytodes species were karyotyped so far. The present paper provides for the first time karyotype analysis of two synanthropic species, Scytodes fusca and Scytodes itapevi. Furthermore, new data on karyotype of Scytodes globula are also provided using conventional and differential cytogenetical procedures. The diploid number in the genus Scyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 11 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…The number and location of NORs were only established, for example, in approximately 30 species of Araneae (Král et al, 2006;Král, 2007;Oliveira et al, 2007;Rodríguez-Gil et al, 2007;Araujo et al, 2008;Stávale et al, 2010Stávale et al, , 2011Dolejš et al, 2011;Král et al, 2011), 17 species of Scorpiones (Schneider et al, 2009a,b;Schneider and Cella, 2010), 3 species of Opiliones (Gorlov and Tsurusaki, 2000;Oliveira et al, 2006;Schneider et al, 2008;Mattos et al, 2013), and two species of Palpigradi (Král et al, 2008). In almost all these species, the NORs were only identified through the use of silver impregnation; however, in an overview of the NOR distribution in Coleoptera, Schneider et al (2007) showed that the results were usually coincident when the chromosomes were examined with both silver impregnation and FISH technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and location of NORs were only established, for example, in approximately 30 species of Araneae (Král et al, 2006;Král, 2007;Oliveira et al, 2007;Rodríguez-Gil et al, 2007;Araujo et al, 2008;Stávale et al, 2010Stávale et al, , 2011Dolejš et al, 2011;Král et al, 2011), 17 species of Scorpiones (Schneider et al, 2009a,b;Schneider and Cella, 2010), 3 species of Opiliones (Gorlov and Tsurusaki, 2000;Oliveira et al, 2006;Schneider et al, 2008;Mattos et al, 2013), and two species of Palpigradi (Král et al, 2008). In almost all these species, the NORs were only identified through the use of silver impregnation; however, in an overview of the NOR distribution in Coleoptera, Schneider et al (2007) showed that the results were usually coincident when the chromosomes were examined with both silver impregnation and FISH technique.…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho). The chromosome preparations were obtained from male and female individuals and stained with Giemsa, following the procedure described by Araujo et al (2008). To identify the constitutive heterochromatin regions the chromosomes were C-banded (Sumner, 1972) and subsequently stained with 4ꞌ-6-diamidino-2-phenylindole (DAPI).…”
Section: Methodsmentioning
confidence: 99%
“…The vouchers were deposited in the Laboratório Especial de Coleções Zoológicas, Instituto Butantan (IBSP), city of São Paulo, state of São Paulo (SP), Brazil (curator A.D. Brescovit). The chromosomal preparations were obtained from ovaries of adult females and from embryos, following the procedure described by Araujo et al (2008): gonads were dissected in physiologic solution for insects (7.5 g Sodium Chloride (NaCl), 2.38 g Sodium phosphate dibasic (Na 2 HPO 4 ), 2.72 g Potassium dihydrogen phosphate (KH 2 PO 4 ), in 1 L of distilled water), transferred to colchicine solution (0.16% in physiologic solution for insects) and left for 2 h. A volume of hypotonic solution (tap water) equal to that of the colchicine solution was added. After 15 min of hypotonization, the material was placed in methanol:acetic acid (3:1) for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…According to Kral et al [2004], 2 species belonging to the Dysderoidea families Oonopidae Simon 1890, and Orsolobidae Cooke 1965, also have holokinetic chromosomes. Most other Haplogynae show predominance of biarmed chromosomes and chromosome numbers between n = 6 + X 1 X 2 and n = 11 + X 1 X 2 , and in some species as high as n = 15 + X [Araujo et al, 2008] and n = 17 + X 1 X 2 Y [Kral et al, 2006]. The majority of the entelegyne spiders show n = 10 + X 1 X 2 to n = 13 + X 1 X 2 , all chromosomes being acrocentric [Suzuki, 1954].…”
Section: Discussionmentioning
confidence: 99%